2014
DOI: 10.1016/j.drugalcdep.2014.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences between predictors of HIV status among PWID in Ukraine

Abstract: Background The HIV epidemic in Ukraine is among the largest in Europe. While traditionally the epidemic has spread through injection risk behavior, sexual transmission is becoming more common. Previous research has found that women in Ukraine have higher rates of HIV and engage in more HIV risk behavior than men. This study extended that work by identifying risk factors that differentially predict men and women’s HIV status among people who inject drugs (PWID) in Ukraine. Methods From July 2010 through July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 52 publications
1
14
0
1
Order By: Relevance
“…Despite evidence supporting OAT, <3% of PWIDs (∼8,000 PWIDs) in Ukraine (Degenhardt et al, 2014; Wolfe, Carrieri, & Shepard, 2010) are receiving OAT (UCDC, 2015). Of those on OAT, approximately 20% are female corresponding to the sex distribution of PWIDs surveyed in Ukraine (Balakireva, 2012; Corsi et al, 2014), and 40% are HIV-infected. On the other hand, incarceration in Ukraine is high (305 people imprisoned per 100,000 population, compared to a mean global incarceration rate of 144 per 100,000), excluding those detained by police or in pre-trial detention (Walmsley, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite evidence supporting OAT, <3% of PWIDs (∼8,000 PWIDs) in Ukraine (Degenhardt et al, 2014; Wolfe, Carrieri, & Shepard, 2010) are receiving OAT (UCDC, 2015). Of those on OAT, approximately 20% are female corresponding to the sex distribution of PWIDs surveyed in Ukraine (Balakireva, 2012; Corsi et al, 2014), and 40% are HIV-infected. On the other hand, incarceration in Ukraine is high (305 people imprisoned per 100,000 population, compared to a mean global incarceration rate of 144 per 100,000), excluding those detained by police or in pre-trial detention (Walmsley, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…61,62 In some contexts, sexual risks may contribute to HIV infection among women who use drugs to a greater extent than among men who inject drugs. 63,64 There are several reasons why sexual transmission of HIV may be greater among women who use drugs compared with men. As the receptive partner, a woman is at greater risk of heterosexual HIV transmission through vaginal or anal sex than a male insertive partner, although risk varies depending on the context and setting.…”
Section: Risk and Vulnerabilitymentioning
confidence: 99%
“…65 In a number of studies, women who use and inject drugs reported having engaged in more sexual HIV risk behaviors than their male counterparts. 60,64,66 Furthermore, there may be greater overlap between women’s sexual and drug use networks, such that women who use drugs are more likely than men who use drugs to have sexual partners who are also drug users. 19,20 …”
Section: Risk and Vulnerabilitymentioning
confidence: 99%
“…In an analysis of PWID at three sites in Ukraine, being female was an independent predictor of HIV status (Booth et al, 2006) and in a study of 16 Ukrainian cities, women were more likely than men to have HIV (Taran, Johnston, Pohorila, & Saliuk, 2011). Women in Ukraine also report more sex- and injection-related risk behaviors than men despite having higher levels of HIV knowledge (Corsi et al, 2014). …”
Section: 1 Introductionmentioning
confidence: 99%
“…Women, particularly those who are dependent on partners for basic subsistence needs, may lack autonomy to effectively negotiate condoms, thereby increasing sexual risk (Jolley et al, 2012; Lambdin et al, 2013; Larney et al, 2015). Compared to their male counterparts, WWID inject more frequently, have overlapping sex and drug partners (Corsi et al, 2014), are more likely to be injected by someone else (often a partner) and to be “second on the needle,” increasing vulnerability to HIV (Springer et al, 2015). Increased stigma, discrimination and greater personal demands to care for others impede access to treatment programs (Des Jarlais et al, 2012; Lambdin et al, 2013; Simmonds & Coomber, 2009).…”
Section: 1 Introductionmentioning
confidence: 99%